Suture Repair and Suspensory Button Fixation of Avulsion Fracture of the Fibular Styloid (Arcuate Fracture) - Surasak Srimongkolpitak, M.D.; Pratchaya Manop, M.D.; Bancha Chernchujit, M.D. (Arthroscopy Techniques)
The fibular head is attached to posterolateral corner structures, which are responsible for stabilization of the varus knee, external rotation, and posterior translation stability. The arcuate sign is a large piece of the fibular head that has avulsed longitudinally from the posterolateral corner. If the fixation system is not sufficient to secure the various stabilities of the knee, it will fail and cause significant knee instability. Concomitant involvement of the proximal tibiofibular joint (PTFJ) may also occur. Many patients, even after fixation, continue to experience persistent proximal knee pain and instability. PTFJ instability is often ignored and misdiagnosed, especially in cases involving the arcuate sign. Numerous fixation systems have been invented and reported in the literature, but they tend to focus solely on the fracture site and anatomic reduction, neglecting PTFJ instability. Suture repair and suspensory button fixation of an avulsion fracture of the fibular styloid (arcuate fracture) aims to establish fixation stability, provide a robust system, minimize the rate of fixation failure, reduce the incidence of implant irritation, and address PTFJ instability.